Appropriate Water and Nitrogen Regulation Promotes Soybean Yield Formation and Improves Water–Nitrogen Use Efficiency - Wang, Yucai; Li, Mao; Zhao, Jin (Agronomy (Basel), 2024)
To address water scarcity and soil damage in the Hexi Oasis irrigation area of China, a study was conducted on regulating water and nitrogen levels for soybean growth under film drip irrigation over two growing seasons (2020 and 2021). Two irrigation levels were tested: mild deficit (W1, 60–70% of field water capacity, FC) and full irrigation (W2, 70–80% of FC), along with three nitrogen levels: low (N1, 60 kg·ha−1), medium (N2, 120 kg·ha−1), and high (N3, 180 kg·ha−1). The control treatment was no nitrogen with full irrigation (W2N0), totaling seven treatments. Results showed that during both growing seasons, soybean plant height reached its peak at the tympanic ripening stage, while the leaf area index (LAI), net photosynthesis rate (Pn), and transpiration rate (Tr) decreased at the tympanic ripening stage. The highest values for the plant height, LAI, Pn, Tr, yield, and the cost–benefit ratio were observed under the W2N2 treatment, significantly outperforming the W2N0 in all aspects (p < 0.05). Over the two-year period, the plant height and LAI were notably higher by 22.86% and 7.09%, respectively, in the W2N2 treatment compared to the W1N1. Full irrigation under N1 and N2 conditions resulted in an enhanced soybean Pn and Tr. However, under N3 conditions, a deficit-tuned irrigation treatment led to a 15.71% increase in the Pn and a 13.34% increase in the Tr on a two-year average. The W2N2 treatment had the highest yield, with a significant 4.93% increase over the W1N3 treatment on a two-year average. The highest rate of change in yield was observed in W1. The two-year cost–benefit ratio and unilateral water benefit reached their peak values in W2N2 and W1N2, respectively. Water use efficiency (WUE) was lower in N1 but significantly increased by 21.83% on a two-year average in W1N3 compared to W1N2. Additionally, W1 had a 14.21% higher WUE than W2 over two years. N3 had the lowest partial factor productivity of nitrogen, which increased by 17.78% on a two-year average in W2N1 compared to W1N1. All nine indicators related to yield formation and water–nitrogen use efficiency showed a positive correlation (p < 0.05) in this study. The highest composite scores were achieved with the W2N2 treatment in both years using the entropy weight and TOPSIS method. Overall, the W2N2 treatment provides a water and nitrogen combination that enhances soybean water and fertilizer efficiency, making it a promising option for high-yield soybean cultivation with water and nitrogen conservation in the Hexi Oasis irrigation area of China. This study offers valuable insights for achieving efficient soybean production while saving water and reducing nitrogen use.